Beamforming and timing design issues for a large aperture array radar applied to atmospheric research - Johansson, Gustav (Luleå tekniska universitet, EISLAB, 2009)
This thesis describes the work done by the author during the development of a Large Aperture Array Radar (LAAR) receiver for the EISCAT 3D project. The main focus was on digital beamforming of a bandpass-sampled wide band signal in base-band and the development of a picosecond-level distributed timing system applicable over hundreds of meters.The next generation of atmospheric research radars all have the common goal of increasing their capabilities with improved versatility and dynamic observation capability. Past radars have mostly been capable only of observing a single volume of the atmosphere at one time, thereby limiting scientists to looking only at small-scale phenomena in the ionosphere. By allowing simultaneous observation of multiple volumes with a high level of accuracy, EISCAT 3D will give scientists a new tool for improving our knowledge about Earth's atmosphere.To provide instantaneous coverage of multiple volumes of the ionosphere, it is necessary to have a multiple beam receiver. The goal of the antenna design in this project was to create digitally steered arrays that will provide easy scalability, such as increasing the number of beams, after the arrays have been built, and make the stringent targets of the radar's capabilities achievable.This thesis is divided into introductory chapters and ve attached papers. The introductory chapters describe the background and some of the reasons behind atmospheric research, Incoherent Scatter Radar (ISR) technology and use, and the EISCAT 3D project, speci cally, the technological challenges encountered on the LAAR receiver. The technologies evaluated and implemented in the test array for the EISCAT 3D project are detailed, and the results and conclusions are discussed.The technological investigation showed that digital beamforming and high accuracy timing are critical issues for the EISCAT 3D LAAR. Digital beamforming is necessary primarily due to the large array size and stringent demands on pointing accuracy, which render the use of analog beamforming ...